EFFECTIVE OF INTERPERSONAL COMMUNICATION AT PT KERETA API INDONESIA (PERSERO) DAOP 4 SEMARANG - Pratiwi, Siska Eka; Farouk, Umar - (Politeknik Negeri Semarang, 2017)
ABSTRACTThe main problem faced by most big companies in running their business, including PT Kereta Api Indonesia (PT KAI) is the less effective of interpersonal communicationin in their business management. This situation often triggers miscommunication among managers, staff, and employees. .This research was conducted to investigate the above mentioned problem. The qualitative approach was chosen to give more specific and operational suggestions. The purposes of this research are to find out influencial and the most infulencial factors on the effectiveness of interpersonal communication at PT KAI. Data colleting methods used in this research were interview, observation and literature.study. The result of this research shows that there are seven effective factors of interpersonal communiation and three ineffective factors of interpersonal communication at PT KAI. The seven effective factors are tolerance, trust, equity, response, emphaty and suporting behavior. The three ineffetive factors are open mindedness, togetherness and honesty. Keywords: efectiveness; interpersonal communication; human resources ABSTRACTMasalah utama yang dihadapi oleh sebagian besar perusahaan besar dalam menjalankan bisnisnya, termasuk PT Kereta Api Indonesia (PT KAI) adalah kurang efektifnya komunikasi interpersonal dalam pengelolaan bisnis mereka. Situasi ini sering memicu miskomunikasi antara manajer, staf, dan karyawan. Penelitian ini dilakukan untuk mengetahui permasalahan di atas. Pendekatan kualitatif dipilih untuk memberikan saran yang lebih spesifik dan operasional. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dan faktor paling infulencial terhadap efektivitas komunikasi interpersonal pada PT KAI. Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi dan literature.study. Hasil penelitian ini menunjukkan bahwa terdapat tujuh faktor efektif komunikasi interpersonal dan tiga faktor yang tidak efektif dalam komunikasi interpersonal pada PT KAI. Tujuh faktor yang efektif adalah toleransi, kepercayaan, kesetaraan, respon, emphaty dan perilaku suporting. Tiga faktor ineffetive adalah keterbukaan pikiran, kebersamaan dan kejujuran. Kata kunci: efektifitas; komunikasi interpersona; sumber daya manusia